2007
DOI: 10.1128/aac.00059-07
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Morbid Obesity on the Single-Dose Pharmacokinetics of Daptomycin

Abstract: The present study characterized the single-dose pharmacokinetics of daptomycin dosed as 4 mg/kg of total body weight (TBW) in seven morbidly obese and seven age-, sex-, race-, and serum creatinine-matched healthy subjects. The glomerular filtration rate (GFR) was measured for both groups following a single bolus injection of [ 125 I]sodium iothalamate. Noncompartmental analysis was used to determine the pharmacokinetic parameters, and these values were normalized against TBW, ideal body weight (IBW), and fat-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 26 publications
3
57
1
3
Order By: Relevance
“…Validation of this approach was undertaken using data from our prior studies with healthy volunteers and critically ill patients (8,18). Consistent with our population model approach above, we observed a trend for positive bias and negative bias around the time point of 1.5 h as the peak sample point.…”
Section: Tablesupporting
confidence: 55%
See 1 more Smart Citation
“…Validation of this approach was undertaken using data from our prior studies with healthy volunteers and critically ill patients (8,18). Consistent with our population model approach above, we observed a trend for positive bias and negative bias around the time point of 1.5 h as the peak sample point.…”
Section: Tablesupporting
confidence: 55%
“…The raw concentration-time data from a previous study evaluating the single-dose plasma PK of daptomycin at 4 mg/kg in 7 normal-weight and 7 morbidly obese healthy female subjects were used (18). The AUC 24 (reference standard) was calculated by integration using the aforementioned 2-compartment model and individual maximum a priori Bayesian probability procedure in ADAPT 5 (14).…”
Section: Methodsmentioning
confidence: 99%
“…Exposure to daptomycin (maximum concentration and area under the curve) following a 4-mg/kg dose is increased by approximately 25 to 30%, respectively, in moderately and morbidly obese healthy patients compared to matched, nonobese controls (14). A subsequent study revealed an approximate 60% increase in maximum concentration and area under the curve following a 4-mg/kg dose in morbidly obese healthy patients compared to normal-weight patients (15). A recent study showed an increased rate of CPK elevation in obese patients, but discontinuation rates remained low (16).…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, one patient (patient 4 from Table 3) with CPK levels of Ͼ1,000 U/liter on combination therapy would have received every-other-day dosing if the CrCl rate was based on their IBW but received daily dosing. The use of actual body weight with the Cockcroft-Gault formula has been demonstrated to overestimate glomerular filtration rate (GFR) in obese patients receiving daptomycin (15). Overestimation of GFR may lead to more frequent dosing of daptomycin than appropriate, increasing drug exposure and subsequent risk of toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies evaluating ABW-dosed daptomycin pharmacokinetics in the morbidly obese (1,4), the AUC increased 30 to 60% compared to in normalweight individuals. Volume of distribution (V) and clearance (CL) were reduced when normalized for weight.…”
mentioning
confidence: 99%